Age effects on the water‐use efficiency and water‐use dynamics of temperate pine plantation forests. Issue 18 (21st July 2015) - Skubel, Rachel; Arain, M. Altaf; Peichl, Matthias; Brodeur, Jason J.; Khomik, Myroslava; Thorne, Robin; Trant, Janelle; Kula, Michelle; Quinton, William; Peters, Daniel L.
Abstract This study analysed age‐related water‐use dynamics across three temperate conifer forest plantations (aged 11, 39 and 74 years, as of 2013, henceforth referred to as TP02, TP74 and TP39, respectively, where the last two digits represent the year of planting) in southern Ontario, Canada, from 2008 to 2013. Eddy covariance‐measured mean evapotranspiration over the growing season (April–October) was 438 ± 19, 392 ± 19 and 323 ± 25 mm at TP39, TP74 and TP02, respectively. Daytime bulk surface conductance was highest and most variable at the TP39 site (8.5 ± 4.0 mm s−1), followed by the TP74 (7.0 ± 2.8 mm s−1) and TP02 (5.4 ± 2.5 mm s−1) sites. Evapotranspiration at all the forests was sensitive to air temperature and tended to decrease with increasing atmospheric dryness. The youngest forest's evapotranspiration was most conservative, which led to an increase in water‐use efficiency throughout the study period, in particular during drought events. The oldest forest was the least restrictive in its water use during drought, which led to lower water‐use efficiency during such events as compared with the younger forests. The oldest forest was thinned in early 2012, when about one third of trees were commercially harvested. No significant change in evapotranspiration or water‐use efficiency was observed at this site following thinning; however, daytime bulk surface conductance declined. Our results suggested that changes in stand structure with forest ageing, such as reduction in stem density and increase in sapwood area, were responsible for differences in soil water demand during drought and non‐drought periods, leading to differences in forest water use. Hence, forest age, because of its structural implications, is an important control on stand‐level water‐use efficiency and forests' response to drought events. Our study suggested that younger forests may be best suited to maximize growth and carbon uptake efficiency under rising air temperatures and increasing precipitation variability as predicted by climate models for eastern North America. Copyright © 2015 John Wiley & Sons, Ltd.